2005
DOI: 10.1002/cphc.200400458
|View full text |Cite
|
Sign up to set email alerts
|

The First Picoseconds in Bacterial Photosynthesis—Ultrafast Electron Transfer for the Efficient Conversion of Light Energy

Abstract: In this Minireview, we describe the function of the bacterial reaction centre (RC) as the central photosynthetic energy-conversion unit by ultrafast spectroscopy combined with structural analysis, site-directed mutagenesis, pigment exchange and theoretical modelling. We show that primary energy conversion is a stepwise process in which an electron is transferred via neighbouring chromophores of the RC. A well-defined chromophore arrangement in a rigid protein matrix, combined with optimised energetics of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
230
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(235 citation statements)
references
References 132 publications
4
230
1
Order By: Relevance
“…Photochemistry Initiated from P. Following excitation of P, the consensus view is that BChl A functions as the initial electron acceptor for P*, forming the P þ BChl A − transient state with a 3 ps risetime (room temperature), but is rapidly converted by electron transfer to BPh A with a 0.9 ps time constant (7). However the overlap of the ground and excited-state optical absorptions of the cofactors has posed challenges for easy verification of this reaction scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Photochemistry Initiated from P. Following excitation of P, the consensus view is that BChl A functions as the initial electron acceptor for P*, forming the P þ BChl A − transient state with a 3 ps risetime (room temperature), but is rapidly converted by electron transfer to BPh A with a 0.9 ps time constant (7). However the overlap of the ground and excited-state optical absorptions of the cofactors has posed challenges for easy verification of this reaction scheme.…”
Section: Discussionmentioning
confidence: 99%
“…The LH2 complexes surround the RC-LH1 complexes in a two-dimensional network and serve as antennas for light harvesting [1,2,7]. Upon optical excitation, the energy is efficiently transferred from LH2 via LH1 to the RC, where it is used to initiate a cyclic electron transfer chain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…24−31 From these studies it is well established that in the RC the absorbed photon-energy is used to drive a series of electron transfer reactions until the secondary ubiquinone (Q B ) has been fully reduced to Q B H 2 ; see Figure 1. 32,33 The dynamics of the energy transfer between the LH1 and the RC has been the subject of countless studies, and the characteristic time constants that have been found range from several picoseconds up to a few nanoseconds. 34−45 In some studies the fluorescent transients were described by up to five decay times that could not always be attributed to distinct processes.…”
Section: ■ Introductionmentioning
confidence: 99%